The effect of chlorogenic acid on the Briggs-Rauscher oscillating reaction - Dacić, Minela; Gojak-Salimović, Sabina (Bulletin of Chemists and Technologists of Bosnia and Herzegovina, 2016)
The Briggs-Rauscher oscillating reaction can be used as test for antioxidant activity of pure compounds or food extracts. Antioxidants are substances that have the ability to neutralize free radicals, which are harmful to human health. Adding the substances with antioxidant ability to the reaction mixture, oscillations temporarily stops, and after a certain time the oscillating reaction starts again. The period without oscillations is known as inhibition time, and it's proportional to the quantity of antioxidant species in reactive mixture. In this study the Briggs-Rauscher reaction was used to measure the antioxidant activity of chlorogenic acid. Inhibition time, duration of reaction and the number of oscillations was determined.